Detection rate of columnar-lining esophagus and adenocarcinoma among the residents of Leningrad region (according to esophagogastroduodenoscopy) - D. I. Vasilevskiy; E. N. Kamalov; S. U. Dvoretskiy; S. S. Skurikhin; D. S. Silantiev; S. N. Mednikov; A. V. Luft; S. F. Bagnenko (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2014)
The incidence of esophageal adenocarcinoma among the population in economically developed countries has been increasing significantly for last three decades. Columnar-lining esophagus (Barrett's esophagus) is one of the proven factors of developing esophagus cancer. The prevalence of Barrett's esophagus and esophageal adenocarcinoma in Russia is not investigated enough. The analysis of the results of 34903 endoscopic examinations of the upper gastrointestinal tract in population of Leningrad region with symptoms of gastric dyspepsia during the period from 2007 to 2013 is presented in this article.